2013
DOI: 10.15388/ekon.2013.0.1412
|View full text |Cite
|
Sign up to set email alerts
|

A Fit Between Individual and Organizational Values and Its Implications for Employees’ Job Satisfaction and Performance

Abstract: The importance of studies on work-related values and attitudes is obvious as values are ascribed a central role in determining the fit between individuals and the employment organization. Responding to the importance of the issue, the paper emphasizes the meaning of the individual and organizational values' fit for the organization, its possibility to become part of strategic planning and a goal for every manager in charge. The aim of the article is to explore the theoretical concepts on values' fit and to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…At the time of selection, these specified values were compared against predefined organisational values to make sure the bank recruited the more suitable employee. The fit between individual values and organisational values supports study by Diskienë and Goštautas (2013).…”
Section: 22diversitysupporting
confidence: 69%
See 1 more Smart Citation
“…At the time of selection, these specified values were compared against predefined organisational values to make sure the bank recruited the more suitable employee. The fit between individual values and organisational values supports study by Diskienë and Goštautas (2013).…”
Section: 22diversitysupporting
confidence: 69%
“…Some interviewees remarked that values originate from an employee's background, while others noted that it is the banks' responsibility to install and build employee values. Confirming sample banks' views Diskienë and Goštautas (2013) indicated that the fit between these two types of values is significant for organisations, for example enhance job satisfaction.…”
Section: 13valuesmentioning
confidence: 89%
“…Previous literature has suggested that successfully meeting job expectations required an environment where trust is high, the quality of supervision is perceived to be good, and the relationship between supervisors and subordinates is positive (Carleton & Clain, 2012; Diskiene & Gostautas, 2013; Finney et al, 2013; Griffin, 2006). Taxman and Gordon (2009) found that consistency, equity, and fairness in employee relations contributed to trust in decision-making processes and, to some degree, trust in the decision maker as well.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The congruence of values indicates that there is alignment between the values of an employee and those of the organization (Diskiene, D. & Gostautas, V., 2013). This refers to the semblance in values held by a person and the organization and how this is reflected in the daily activities of an employee (Vveinhardt, J.…”
Section: Values Congruencementioning
confidence: 99%
“…Studies also show that values congruence contributes to the reduction of human resource-related issues such as staff turnover, unethical employee behavior, using time in the workplace for activities unrelated to one's work, stress, and anxiety (Gulbovaitė, 2017). Employees give more importance to selecting organizations with which they have a match of values over how much they will be compensated for their work (Diskiene, D. & Gostautas, V., 2013).…”
Section: Values Congruencementioning
confidence: 99%